Academic Writing for Publication Purposes and Machine Translation: Is the Symbiosis Possible? - O. L. Dobrynina (Moscow Polytechnic University, 2022)
The abstracts in Russian and in English are written according to certain rules. For articles written in Russian, an abstract in English is the only means of informing the world scientific community about the authors' research results. However, the quality of abstracts written in Russian and then translated into English does not always meet the criteria for readability and comply with the accepted academic and publication conventions. This situation might result from the intensive usage of machine translation (MT) systems by authors who do not take into account the guidelines for the input text quality and the limitations inherent in MT systems. The author analyzed the requirements for the input texts and some typical errors in the target ones. The article describes the stages of training masters, postgraduate students and university staff in the effective use of MT systems. The training is based on a bilingual approach, which implies a constant comparison of vocabulary, grammar and style in the native and English languages. The author comes to the conclusion that the effective use of MT systems for writing an abstract in English is possible if the authors have the command of Russian and English at the level sufficient for a concise and unambiguous expression of their thoughts and ideas. Self-censoring is a prerequisite for creating a text that is "understandable" for MT systems. Students must follow simple rules: write sentences of 15-20 words; express one thought per one sentence; use more active verbs; choose nouns that express a specific concept; exclude unnecessary words. At the post-editing stage, learners can use the tools available on the Internet, which allow not only editing the target text, but also will enable learners to acquire independent editing skills.